The Institutional Dimension of Sustainable Development in Brazil (Global Journal of Human-Social Science, 2024)
This article aims to review the state of the art of the institutional dimension of sustainable development focusing on the portrayal of this dimension through indicators in Brazil The research employs a theoretical-argumentative methodology for exploratory analysis of sustainable development in Brazil from an institutional perspective The procedures of bibliographic research and document analysis are used in the discussion As a result it is confirmed that the institutional dimension of sustainable development reveals a generic framework of institutional efforts and capacities This dimension is poorly portrayed by sustainability indicators due to its complexity and difficulty in collecting primary data Accordingly the strengthening of governance is suggested as a solution for the improvement of the institutional framework in the country
Keywords: sustainable development; institutional dimension; brazil; governance; indicators